PERTUMBUHAN STEK KUNYIT PUTIH (Curcuma zedoaria Berg.) AKIBAT PERLAKUAN PUPUK KANDANG SAPI - Ariyanto, Shodiq Eko; Arini, Nindya; Sedjati, Subur (Universitas Muria Kudus, 2022)
White turmeric is one of the traditional medicinal ingredients that can inhibit the proliferation of cancer cells and has various other benefits. Turmeric grows well in loose, fertile soil, contains organic matter, and is well drained. Manure is an organic fertilizer derived from livestock manure, either in the form of solids (faeces) mixed with food residue or urine, has the ability to improve the physical, chemical, and biological properties of the soil. The purposes of this study were (1) to determine the effect of giving cow manure to white turmeric suppression, and (2) to determine the dose of cow manure used. The design used in this study was a randomized block design consisting of five levels of treatment with manure doses. cows per polybag, namely: A (0 g), B (100 g), C (200 g), D (300 g) and E (400 g). The results of the study of cow manure treatment had a significant effect on shoot growth rate, shoot length, number of leaves and growth